Poles in Aid: Polskie organizacje pozarządowe w pomocy rozwojowej a dyplomacja publiczna - Zalas-Kamińska, Katarzyna (Księgarnia Akademicka Publishing, 2019)
POLES IN AID: POLISH NGOS IN DEVELOPMENT AID AND PUBLIC DIPLOMACY This book identifies how Polish development aid, and in particular its elements implemented in cooperation with NGOs between 2004 and 2012, has begun to reflect the assumptions of Polish public diplomacy. The author indicates that the issues related to the promotion of democracy and the transfer of know-how in the field of successful transformation – realized with the participation of non-governmental sector – were common for both development aid and public diplomacy. This corresponded to the forming concept of building the image of Poland as a country of smart democratic changes. What is more, it identified the potential of the NGOs power, especially soft power, which – when skillfully used – could become a component of the Polish democratization agenda after 2012.